Kontribusi TGH Lalu Muhamad Nuh dalam Upaya Meningkatkan Kecerdsan Spiritual Santri Qudwatussolihin Pemondah Pandan Wangi: The Contribution of TGH Lalu Muhammad Nuh in Efforts to Increase the Spiritual Intelligence of Qudwatussolihin Students in Pandan Wangi - Sirajun Nasihin; Zaibun Irmawadi (Al-Faizi : Jurnal Politik, Hukum dan Bisnis, 2025)
Spiritual intelligence is the human ability to actualize divine values as a manifestation of their activities in daily life. Nowadays, it is not enough for humans to only have intellectual intelligence and emotional intelligence, but must be equipped with spiritual intelligence which is obtained by getting closer to Allah SWT.The aims of this research are. (1) to determine the Kontribute of TGH in increasing spiritual intelligence as role models for students at Qudwatussolihin Islamic boarding school,(2) to determine the kontribut of TGH Lalu Muhamad Nuh in increasing spiritual intelligence as motivators for students at Qudwatussolihin  Islamic boarding school, (3) to determine the contribute TGH Lalu Muhamad Nuh  in increasing spiritual intelligence as an educator for students at Qudwatussolihin Pondok.[13.34, 31/1/2024] Zaibun Irmawad: This research uses a qualitative approach with a case study type of research.Data collection techniques: interviews, documentation and observation. Data analysis uses data reduction techniques, data display, and drawing conclusions. [13.34, 31/1/2024] Zaibun Irmawadi: From the research results it was found that (1) The contribute of TGH Lalu Muhamad Nuh in increasing spiritual intelligence as role models for students at the Qudwatussolihin cottage is that students are required to always be kind and grateful to local residents. The students are also taught tepo seliro among themselves. Apart from that, if the students make a mistake, they must be ready to admit their mistake and immediately apologize. (2) The contribute of the TGH Lalu Muhamad Nuh in increasing spiritual insight as a motivator for the tantri at the Qudwatussolihin cottage is that there are many ways to do this. The ustadz/ustadzah of Qudwatussolihin Islamic Boarding School so that students can become motivators for themselves and others, namely by teaching the meaning of dui belief, learning toto control emotions, learning to speak well and also creatively, (3) The kontibute of TGH Lalu Muhamad Nuh in increasing spiritual intelligence as educators to the students at the Qudwatussolihin cottage, namely always emphasizing istiqomah to the students.